2022
DOI: 10.1186/s12964-022-00879-3
|View full text |Cite
|
Sign up to set email alerts
|

The ROCK-ezrin signaling pathway mediates LPS-induced cytokine production in pulmonary alveolar epithelial cells

Abstract: Background Ezrin/radixin/moesin (ERM) proteins are members of the protein 4.1 superfamily and function as linkers that connect the actin cytoskeleton to the plasma membrane of cells. ERM also play critical role in the Lipopolysaccharide (LPS)-induced inflammatory response. However, the signaling mechanisms involved in this process remain unclear. In this study, we aimed to investigate the potential role of the rho-associated coiled-coil containing protein kinase (ROCK) pathway in LPS-induced ez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…LPS is a type of endotoxin-like biomolecule that exists in the outer membrane of many bacteria, which had been found to induce plethora of immune and inflammatory reactions 42 , 43 . The production of various cytokines, such as TNF, IL-1, IL-6, and other inflammatory factors stemmed from the interaction between LPS and host cells may inevitably leads to prolonged inflammation and cell damage 44 , 45 . Hence, we infer that NETs not only function to eliminate LPS invasion, but may also play a role in protecting the host from pathogenic bacterial invasion through activating and amplifying the response of human airway cells to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is a type of endotoxin-like biomolecule that exists in the outer membrane of many bacteria, which had been found to induce plethora of immune and inflammatory reactions 42 , 43 . The production of various cytokines, such as TNF, IL-1, IL-6, and other inflammatory factors stemmed from the interaction between LPS and host cells may inevitably leads to prolonged inflammation and cell damage 44 , 45 . Hence, we infer that NETs not only function to eliminate LPS invasion, but may also play a role in protecting the host from pathogenic bacterial invasion through activating and amplifying the response of human airway cells to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Ezrin phosphorylation sites can be regulated by several signaling pathways and perform different physiological functions upon activation and phosphorylation ( Yin and Schnoor, 2022 ). Initial studies demonstrated that the critical T567 on C-ERMAD could be phosphorylated by Rho-kinase (ROCK) ( Ding et al, 2022 ), STE20-like protein kinase (SLK) ( Garland et al, 2021 ), lymphocyte-oriented kinase (LOK) ( Senju and Tsai, 2022 ) and protein kinase C(PKC) ( Khan et al, 2022 ) both in the laboratory and in living organisms. Ezrin Y145, Y353 and Y477 can be modified by phosphorylation through the action of Src kinases and the intrinsic Tyr kinase activity of receptors for epidermal growth factor, hepatocyte growth factor and Platelet-derived growth factor ( Huang et al, 2018 ; Derouiche and Geiger, 2019 ; Rainey et al, 2020 ).…”
Section: The Post-translational Modifications Of Ezrinmentioning
confidence: 99%
“…ROCK1 has been shown to phosphorylate Ezrin at Thr567 [ 148 ]. Interestingly, Ezrin can act upstream and downstream of ROCK1 in the RhoA/ROCK signaling pathway, where ROCK1 activates Ezrin, dissociates RhoGDI from RhoA, and subsequently activates RhoA/ROCK [ 149 ]. In Jurkat cells, Fas-mediated apoptosis is regulated by the Rho/ROCK-dependent phosphorylation of Ezrin and Moesin, where Rho or ROCK inhibition prevents their phosphorylation, disrupting the formation of Fas aggregates and subsequent apoptosis induction [ 150 ].…”
Section: Ezrin Interacts With Metastasis-related Proteinsmentioning
confidence: 99%